Investigation of O3-precursor relationship nearby oil fields of Shandong, China. (1st February 2023) - Li, Liming; Zheng, Zhensen; Xu, Bo; Wang, Xinhua; Bai, Zhipeng; Yang, Wen; Geng, Chunmei; Li, Kangwei
Abstract: Oil exploitation can release a large amount of volatile organic compounds (VOCs), which play an important role in tropospheric chemistry and contribute to ozone (O3 ) and secondary organic aerosols (SOA) formation in its surrounding environment. To evaluate the impact of oil exploitation on tropospheric O3 formation, a comprehensive field campaign on O3 and its precursors (VOC, NOx, etc) was conducted during May–September 2019 in a site nearby oil fields of Shandong province, China. The average mixing ratio of the total VOC (TVOC) was 59.2 ± 30.2 ppbv, and alkanes contributed 78% of TVOC (with C2 –C5 alkanes as the main contributors). A 0-D box model incorporating the latest Master Chemical Mechanism (MCMv3.3.1) was applied using observations as constraints, and we found that the O3 formation was mainly under transitional and VOC-limited regime for high-O3 and low-O3 periods, respectively. The relative incremental reactivity (RIR) values from individual AVOC species were basically consistent with those calculated from OH reactivity, and both metrics suggested that C3 –C5 alkanes, C2 –C5 alkenes, and C7 –C9 aromatics were the most sensitive VOC species to O3 formation. The results from empirical kinetic modeling approach (EKMA) indicated large day-to-day variations of photochemical regimes, which covered VOC-limited, transitional, and NOx-limited regimes on a daily basis during the five-month campaign. The emission reduction modeling with a large number of scenarios further suggested that the reduction of anthropogenic VOC and NOx at a ratio of 1:3 would be a more practical strategy for mitigation of the local O3 pollution. These results could provide a basis for understanding the O3 -precursor relationship nearby the oil field area, and the derived policy-relevant emission control strategy could provide guidance for other oil field in Shandong and other regions to take effective O3 control measures. Graphical abstract: Image 1 Highlights: O3 and its precursors were investigated in a receptor site nearby oil fields of China. Most sensitive VOC species to O3 formation were identified based on different metrics. 0-D box model showed large day-to-day variations of O3 formation regime for the site. A synergic reduction plan to NOx and AVOC was developed for local area O3 mitigation.